2020
DOI: 10.1177/1087054720906514
|View full text |Cite
|
Sign up to set email alerts
|

Interventions for Adolescents With ADHD to Improve Peer Social Functioning: A Systematic Review and Meta-Analysis

Abstract: Objective: Peer social functioning difficulties characteristic of ADHD persist into adolescence, but the efficacy of interventions for this age group remains unclear. Method: A systematic search of nonpharmacological interventions for adolescents with ADHD (10–18 years) identified 11 trials addressing social functioning, of which eight were included in meta-analyses. Results: Random effects meta-analyses of four randomized trials found no differences in social functioning between treatment and control groups b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 72 publications
3
41
0
Order By: Relevance
“…Recent systematic review evidence ( Dahl et al, 2020 ) has concluded that psychoeducation interventions for parents and teachers can lead to improvements in behavior in CAYP with ADHD and that there is little evidence in favor of behavioral interventions improving peer social functioning in CAYP with ADHD ( Morris et al, 2020 ). This review adds to the existing evidence base by only including studies evaluating interventions that involve a psychoeducational component and specifically assessing the impact these interventions have upon social skills in CAYP with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…Recent systematic review evidence ( Dahl et al, 2020 ) has concluded that psychoeducation interventions for parents and teachers can lead to improvements in behavior in CAYP with ADHD and that there is little evidence in favor of behavioral interventions improving peer social functioning in CAYP with ADHD ( Morris et al, 2020 ). This review adds to the existing evidence base by only including studies evaluating interventions that involve a psychoeducational component and specifically assessing the impact these interventions have upon social skills in CAYP with ADHD.…”
Section: Discussionmentioning
confidence: 99%
“…To date, interventions for ADHD-related difficulties have had limited success in the adolescent age group, with organizational interventions the only domain that is well-established (Evans et al, 2018). In contrast, there is limited evidence for interventions targeting social functioning in this age group (Morris et al, 2020; Storebø et al, 2019). Ensuring that functional changes are able to be measured with precision and specificity is essential in developing and trialing interventions, as well as tracking improvements in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Best practice guidelines for the diagnosis and management of ADHD mandate teacher involvement, typically through the completion of rating scales of a child or adolescent’s symptoms, behavior, and functional impairment (Pelham et al, 2005; Wolraich et al, 2019). Teachers provide a unique perspective on functional domains such as problematic behavior, social functioning, and academic performance, and their reports are used in intervention research (DuPaul et al, 2012; Morris et al, 2020; Sonuga-Barke et al, 2013; Staff et al, 2020). Teacher-reported scores are often esteemed as a more rigorous measurement of outcomes than parent- or self-reported scores, as teachers may be blinded to intervention condition (e.g., Sonuga-Barke et al, 2013).…”
mentioning
confidence: 99%
“…Further, the current study is now one of three longitudinal studies demonstrating a positive link between social skills and substance use among adolescents with ADHD (i.e., Molina et al, 2012; Sibley et al, 2014), suggesting that treatments that improve social skills for this group may have negative downstream effects. However, treatments targeting social skills among youth with ADHD have been minimally effective (see Morris, Sheen, Ling, Foley, & Sciberras, 2020). As efforts continue to improve the effectiveness of social skills training and emotion regulation interventions for youth with ADHD, our findings suggest that these treatments should incorporate a parenting component to potentially buffer against possible iatrogenic effects.…”
Section: Discussionmentioning
confidence: 99%